Inhibition of Prostate Smooth Muscle Contraction by Inhibitors of Polo-Like Kinases - Hennenberg, Martin; Kuppermann, Paul; Yu, Qingfeng; Herlemann, Annika; Tamalunas, Alexander; Wang, Yiming; Rutz, Beata; Ciotkowska, Anna; Strittmatter, Frank; Stief, Christian G.; Gratzke, Christian (Frontiers in Physiology, 2018)
Background: Prostate smooth muscle contraction plays an important role for pathophysiology and treatment of male lower urinary tract symptoms (LUTS) but is incompletely understood. Because the efficacy of available medication is limited, novel options and improved understanding of prostate smooth muscle contraction are mandatory. Recently, a possible role of polo-like kinase 1 (PLK1) has been suggested for smooth muscle contraction outside the lower urinary tract. Here, we examined effects of PLK inhibitors on contraction of human prostate tissue. Methods: Prostate tissues were obtained from radical prostatectomy. RT-PCR, Western blot and immunofluorescence were performed to detect PLK expression and phosphorylated PLK. Smooth muscle contractions were induced by electric field stimulation (EFS), α1-agonists, endothelin-1, or the thromboxane A2 analogue U46619 in organ bath. Results: RT-PCR, Western blot, and immunofluorescence suggested expression of PLK1 in the human prostate, which may be located and active in smooth muscle cells. EFS-induced contractions of prostate strips were reduced by SBE 13 (1 µM), cyclapolin 9 (3 µM), TAK 960 (100 nM), and Ro 3280 (100 nM). SBE 13 and cyclapolin 9 inhibited contractions by the α1-agonists methoxamine, phenylephrine, and noradrenaline. In contrast, no effects of SBE 13 or cyclapolin 9 on endothelin-1- or U46619-induced contractions were observed. Conclusions: Alpha1-adrenergic smooth muscle contraction in the human prostate can be inhibited by PLK inhibitors. PLK-dependent signaling may be a new pathway, which promotes α1-adrenergic contraction of prostate smooth muscle cells. As contractions by endothelin and U46619 are not susceptible to PLK inhibition, this reflects divergent regulation of adrenergic and non-adrenergic prostate smooth muscle contraction.